C-Jun regulates flotillin 2 transcription to benefit viral accumulation in insect vectors. (January 2023) - Zhao, Wan; Wang, Wei; Xiao, Yan; Cui, Feng
Abstract: The c-Jun N-terminal kinase (JNK) signaling pathway plays a critical role in viral infection in host cells. In addition to triggering immune reactions against pathogens, the JNK signaling pathway has also been found to benefit viral infection. Our previous work showed that JNK activation facilitated rice stripe virus (RSV) accumulation in the insect vector small brown planthopper, but the underlying mechanisms remain elusive. Here, we revealed a link between JNK activation and the transcriptional upregulation of the plasma membrane protein flotillin 2, which mediates RSV cell entry. c-Jun, a downstream substrate of JNKs, was identified as a transcription factor that targets the promoter of flotillin 2  at three binding sites. Phosphorylated c-Jun, especially at the serine 63 site, promoted the transcriptional activity of c-Jun on flotillin 2 . JNK activation or inhibition affected c-Jun phosphorylation status and flotillin 2 expression. In the midguts of planthoppers, RSV infection significantly increased flotillin 2 expression and the phosphorylation level of JNKs and c-Jun. Manipulation of JNK status impacted viral acquisition in midgut cells. These findings reveal a new regulatory mechanism of the JNK signaling pathway and shed light on the virus-supportive effect of this pathway. Graphical abstract: Image 1 Highlights: c-Jun is a transcription factor that targets the promoter of flotillin 2. Phosphorylated c-Jun promotes the transcriptional activity of c-Jun on flotillin 2. RSV activates JNKs to upregulate flotillin 2 expression for improving viral acquisition in midgut cells of planthoppers.